Teacher's Strategy in Class 2 Al-Quran Hadith Learning at Madrasah Ibtidaiyah: Strategi Guru pada Pembelajaran Al Quran Hadits Kelas 2 di Madrasah Ibtidaiyah - Lutvia, Lutvia; Nadlif, Ainun (Indonesian Journal of Education Methods Development, 2023)
In the implementation of educating and realizing there are many very complicated cycles, so to find out how to run well, successfully and productively and to achieve a goal that is truly formed, a good learning strategy is needed. In school, Al-Qur'an Hadith is one of the strict subjects which is the basic source of regulation in Islam. So students must have the choice to master these subjects as much as possible to make an age that accepts, fears Allah SWT and has a respectable personality. The problem is that there are enough teachers of the Qur'an and Hadith at this time. Starting from the arrangement, especially the arrangement of inspiration by educators to students to arouse the spirit of learning, educational experiences that use several strategies, to assessment and at the same time finding children who do not have the option to read and study. compose the Koran.